2002
DOI: 10.1096/fj.01-0829fje
|View full text |Cite
|
Sign up to set email alerts
|

DNA oligonucleotide treatment corrects the age‐associated decline in DNA repair capacity

Abstract: Age-related decline in DNA repair capacity (DRC) is associated with decreased constitutive levels of p53 and other nucleotide excision repair proteins. To determine whether pretreatment of cells with small DNA oligonucleotides compensates for decreased DRC in the elderly, fibroblasts from donors of different ages were pretreated with thymidine dinucleotide (pTT), a 5' phosphorylated 9 base oligonucleotide (p9mer) or diluent alone for 48 h, then UV-irradiated with solar-simulated light. Western blot analysis re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
62
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(75 citation statements)
references
References 62 publications
(107 reference statements)
10
62
0
Order By: Relevance
“…S1, a and b). UV irradiation up-regulated p53 total and p53 Ser15 levels by 8 h and through 24 h and up-regulated COX-2 within 24 h, as reported previously (25,50,55), in diluent-treated cells (Fig. 1b and Fig.…”
Section: T-oligo Pretreatment Down-regulates Base-line and Uvb-inducesupporting
confidence: 88%
See 1 more Smart Citation
“…S1, a and b). UV irradiation up-regulated p53 total and p53 Ser15 levels by 8 h and through 24 h and up-regulated COX-2 within 24 h, as reported previously (25,50,55), in diluent-treated cells (Fig. 1b and Fig.…”
Section: T-oligo Pretreatment Down-regulates Base-line and Uvb-inducesupporting
confidence: 88%
“…Cell Culture-Primary human neonatal fibroblast and keratinocytes cultures were established as described (49,50). Cells were incubated at 37°C in 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…The functional damage to the stratum corneum induced by ionizing radiation occurs with a delayed course, starting within a mean period of 11 days and reaching maximal values after a mean period of 27 days (range, 13-75 days) 12 . Moreover, Goukassian et al, 2002 reported that pTpT treated skin of all mice showed spongiosis and sunburn cells, which was prominent in Xeroderma pigmentosa diseased mice, consistent with compensatory hyperplasia 13 . The current study confirmed that presence of spongiosis, which increased the thickening of epidermis by 52.6% in the fourth day of irradiation when pTpT was previously applied with 0.5 Gy.…”
Section: Discussionmentioning
confidence: 67%
“…36 Reduction in DNA repair capacity appears to increase the risk of BCC development specifically because young individuals with a history of BCC have lower DNA repair capacity than age-matched controls. 36 Our group has previously shown that pTT treatment corrects the age-associated decline in DNA repair capacity 37 at least in part through p53 activation, known to play a key role in DNA damage repair, with up-regulation of multiple DNA repair proteins, some but not all of which are induced by p53. 38,39 Within 24 to 48 hours pTT treatment enhances DNA repair and induces other photoprotective responses in cultured cells, hairless mice, and human skin explants.…”
mentioning
confidence: 99%
“…42 In this article we demonstrate that 8-hydroxy-2Ј-diguanosine (8-oxo-dG), known to be generated by UV-induced oxidative DNA damage, 43 was reduced significantly in pTT-versus vehicle-treated UVirradiated murine skin. This suggests that in vivo pTT not only up-regulates nucleotide excision repair, 8,28,37 but may also up-regulate base excision repair and/or reduce reactive oxygen species by increasing superoxide dismutase levels. p53 mutation is an early event in skin carcinogenesis and occurs in 40 to 60% of BCCs.…”
mentioning
confidence: 99%